Grammatical and syntactical approaches in architecture emerging research and opportunities - Lee, Ju Hyun; Ostwald, Michael J. (IGI Global, 2020)
"This book illustrates syntactically derived and grammatically interpolated approaches for architectural configuration, analysis, and design generation"
Keywords: Architecture / Philosophy; Architecture / Methodology